Coal Mine Slope Stability Analysis Using the Rock Mass Rating (RMR), Slope Mass Rating (SMR) Method, and Morgenstren-Price Limit Equilibrium for the Low Wall Pit Area Y PT. Bina Sarana Sukses, Lahat Regency, South Sumatra - Najib Najib; Nanda Putri Belia; Ahmad Syauqi Hidayatillah; Kevin Setyo Adi Nugroho (Diponegoro University, 2024)
Open pit mining has a complex connection to excavation and stockpiling operations, which can potentially induce slope instability. The analysis of slope stability is crucial to prevent slope failure, which has the potential to result in major losses. The study on slope stability was performed at the low wall pit Y area of PT. Bina Sarana Sukses site MAS in Lahat Regency. This research aimed to analyze the rock mass classifications, determine the safety factor values, and provide recommendations for mitigating landslide occurrences. The techniques employed in this study include the RMR and SMR methods for assessing the susceptibility of landslides, collectively with the Morgenstern-price limit equilibrium approach for estimating the stability of the slope. Based on the analysis of the rock mass rating (RMR) and slope mass rating (SMR), Block B2 exhibits a 20% likelihood of experiencing landslides, specifically due to block joint characteristics. On the other hand, Blocks B4 and B5 show a 40% potential for landslides, primarily associated with flat or wedge-type block joints. The force produced by friction under saturated conditions is comparatively lower than that observed under dry conditions. During the final design phase in 2022, it was observed that Blocks B4 and B5 exhibit critical and dangerous safety factors when saturated. Hence, the proposal has been suggested to enhance slope stability. Further, it is recommended to monitor the geotechnical piles periodically. We hope this research results as a valuable resource for evaluating and assessing slope stability, including artificial and natural slopes.